2020
DOI: 10.3389/fgene.2020.00416
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Privacy and Data Protection: A Review of Chinese Direct-to-Consumer Genetic Test Services

Abstract: Background: The existing literature has not examined how Chinese direct-to-consumer (DTC) genetic testing providers navigate the issues of informed consent, privacy, and data protection associated with testing services. This research aims to explore these questions by examining the relevant documents and messages published on websites of the Chinese DTC genetic test providers. Methods: Using Baidu.com, the most popular Chinese search engine, we compiled the websites of providers who offer genetic testing servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…To address the first question on promises made by genetic talent testing companies, I draw on materials from these companies such as marketing materials, press releases, and sample reports. I used a list of DTC-GT companies from Du and Wang (2020) and downloaded material from websites of 48 companies in May 2020. 3 Thirty-two (67%) companies were founded after 2010, and most are located in major cities such as Beijing, Shanghai, Hangzhou, and Shenzhen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the first question on promises made by genetic talent testing companies, I draw on materials from these companies such as marketing materials, press releases, and sample reports. I used a list of DTC-GT companies from Du and Wang (2020) and downloaded material from websites of 48 companies in May 2020. 3 Thirty-two (67%) companies were founded after 2010, and most are located in major cities such as Beijing, Shanghai, Hangzhou, and Shenzhen.…”
Section: Methodsmentioning
confidence: 99%
“…3. Du and Wang (2020) analyzed websites of 83 companies in September 2019. By May 2020, 14 websites were either broken or the companies no longer existed, 8 companies were contract research organizations that did not sell services to consumers, and 13 of these services were not mail-in products but were conducted out of brick-and-mortar labs; 48 of these were direct to consumer (DTC) in the conventional sense.…”
Section: Fundingmentioning
confidence: 99%
“…In China, meanwhile, Du and Wang (2020) examined the measures of privacy and data protection by Chinese DTC-GT services. They concluded that the industry was mainly self-regulated and that the country needed a comprehensive legal framework for regulating DTC-GT considering its rapid spread (Du and Wang, 2020).…”
Section: Academic Concerns About Dtc-gtmentioning
confidence: 99%
“…It should be stressed thatcontrary to European provisionsthese Chinese instruments focus on the collective security of the community and not on protection of individuals, as evidenced also by involvement of the ministry in charge of technological development along the ministry responsible for health in preparation of the provisions. On the other hand, recent amendments to the provisions are more balanced, including protection of individuals [67], as well as for health care data protection, Chinese law also prohibits their transfer abroad (including a prohibition of storing such data on foreign servers), but still, "currently, the Chinese DTC genetic testing business is running in a regulatory vacuum, governed by self-regulation" [68].…”
Section: Genetic Resources […] May Jeopardize National Security Natio...mentioning
confidence: 99%